2015
DOI: 10.5194/acp-15-2327-2015
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant production from source-oriented particulate matter – Part 1: Oxidative potential using the dithiothreitol (DTT) assay

Abstract: Abstract. Recent epidemiological evidence supports the hypothesis that health effects from inhalation of ambient particulate matter (PM) are governed by more than just the mass of PM inhaled. Both specific chemical components and sources have been identified as important contributors to mortality and hospital admissions, even when these end points are unrelated to PM mass. Sources may cause adverse health effects via their ability to produce reactive oxygen species in the body, possibly due to the transition m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 69 publications
7
54
4
1
Order By: Relevance
“…The higher DTT activity of the upper submicron mode compared to the <0.49 µm mode is in agreement to Charrier et al (2015) [47], who found that submicron fine PM (0.17 µm ≤ Dp ≤ 1.0 µm) typically has a larger mass-normalized oxidative potential than UFPs (PM 0.17 ).…”
Section: Size Distribution Of Dtt Activitysupporting
confidence: 89%
See 2 more Smart Citations
“…The higher DTT activity of the upper submicron mode compared to the <0.49 µm mode is in agreement to Charrier et al (2015) [47], who found that submicron fine PM (0.17 µm ≤ Dp ≤ 1.0 µm) typically has a larger mass-normalized oxidative potential than UFPs (PM 0.17 ).…”
Section: Size Distribution Of Dtt Activitysupporting
confidence: 89%
“…Recently, [51] studying the distribution of water-soluble DTT activity in ten size fractions within the range 0.056-18 µm, found that, at the roadside Apparently, the lowest DTT activity occurred in fraction <0.49 μm implying that the quasi-UFP mode, that accounted for 57% and 53% of the bulk PM mass at the UT and the UB site, respectively ( Figure 2b) are less enriched with water-soluble DTT-active substances than larger particles. The higher DTT activity of the upper submicron mode compared to the <0.49 μm mode is in agreement to Charrier et al (2015) [47], who found that submicron fine PM (0.17 μm ≤ Dp ≤ 1.0 μm) typically has a larger mass-normalized oxidative potential than UFPs (PM0.17).…”
Section: Size Distribution Of Dtt Activitysupporting
confidence: 89%
See 1 more Smart Citation
“…Based on the chemical composition and the assumption that DTT activities of quinones and transition metals are additive, previous studies have attempted to reconstruct the overall OP in ambient particles based on the chemical composition (Charrier and Anastasio, 2012;Charrier et al, 2015). However, addition of a transition-metal chelator did not result in significant changes in the expression of inflammatory biomarkers (Donaldson et al, 2001), suggesting that oxidative activities from different transition metals may not be additive.…”
Section: Op Changes Upon Mixing With Cumentioning
confidence: 99%
“…ROS include a variety of oxidants such as superoxide (O q − 2 ), hydroxyl radical ( q OH), and hydrogen peroxide (HOOH), which could either be introduced into human body directly from inhaled PM or generated by targeted cells (Nel et al, 1998;Pöschl and Shiraiwa, 2015;Rhee, 2006;Verma et al, 2015b). The generation of ROS during multiphase in-teractions between air pollutants and the human respiratory tract is closely related to the chemical composition, since the combination of various pollutants may influence chemical reactivity as well as bioavailability of PM while having synergistic or nonlinear influences on its OP (Antiñolo et al, 2015;Charrier et al, 2015;Fang et al, 2015;Shiraiwa et al, 2012;Xiong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%